The Islamic Worldview and Customary Law on Patterns of Inheritance Distribution - Al-Hakim, Shidiq; Fauzi, Unang; Tanjung, Hendri (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study discusses customary issues that arise in Indonesian culture, namely the inheritance distribution tradition in the patrilineal inheritance system in Betawi culture and the matrilineal inheritance system in Minangkabau culture. These two traditions highlight different approaches to inheritance and gender roles in society. Through interviews with traditional leaders, researchers seek to understand the concept of sharia in order to maintain a more beneficial cultural continuity. The triangulation method was used to verify information from respondents in various contexts to compare ethnic views and Islamic concepts. The results of the study show differences in understanding and its impact on economic conditions. The inheritance distribution tradition of the Betawi tribe reflects cultural adaptation to values of gender equality that are in line with the Islamic Worldview, but still faces challenges in fully integrating Islamic principles. Meanwhile, the Minangkabau matrilineal inheritance system emphasizes the role of women in the family structure and inheritance, but creates complexity in asset management.